Accounting for financial instruments with characteristics of debt and equity: finding a way forward. (16th August 2018) - Fargher, Neil; Sidhu, Baljit K.; Tarca, Ann; van Zyl, Warrick
Abstract: Accounting for compound financial instruments, that is those with characteristics of both debt and equity, has challenged accounting standard setters for decades. The principles developed to distinguish liabilities and equity and the application of these principles in IAS 32 have been widely criticised. In 2016–2017, the IASB was engaged in a project to improve IAS 32. Our study presents research that is relevant to the issues faced by standard setters, related to improving the definitions and enhancing presentation and disclosure of liabilities and equity. We discuss studies investigating the effects of the accounting classification requirements on firms' financing choices and on users' decision‐making, to examine the question, 'Does the distinction matter?' We then explore various approaches that may be pursued by the standard setters to improve accounting in this area and identify areas for future research.